Implementasi Kebijakan Jaminan Kesehatan Nasional di Rumah Sakit Umum Daerah Kota Bandung - Novia Yuliannisa Nuurjannah (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2021)
The National Health Insurance / JKN aims to protect all Indonesian residents in the insurance system, so that the government can meet the basic needs of proper public health, to support this policy to form the Social Security Administering Body / BPJS Kesehatan. This study seeks to identify and analyze internal and external factors as well as determine the right strategy in achieving the successful implementation of the national health insurance policy in Bandung City Hospital. Qualitative with a descriptive research approach. Using primary data and secondary data. Eleven informants in the study were obtained directly from related officials and JKN participants, who were conducted with structured and semi-structured interviews as well as regulations, data related to the implementation of JKN. The data were analyzed using the data analysis model of Milles and Huberman and presented in the form of a SWOT analysis diagram and a table of priority strategic issues. Implementation of the JKN policy was not optimal, the MOU from BPJS Kesehatan was made unilaterally and was unclear, this had an impact on claims that were not paid, arrears in payments from BPJS to hospitals affected the availability of drugs and communication between BPJS Kesehatan and hospitals related to regulations was not going well as well as the role of BPJS Kesehatan as an insurance party that does not socialize to the community as beneficiaries, where the community does not understand the types of diseases and types of medicines that are guaranteed and not guaranteed.